Olfactory Fossa Depth Assessment Based on Keros Classification using Computed Tomography - Mubina Lakhani; Nuzhat Hassan; Arsalan Manzoor; Muhammad Ali; Madeeha Sadiq (Journal of Bahria University Medical and Dental College)
ABSTRACT: Objective: To evaluate the olfactory fossa depth and to categorize it according to Keros classification. Methodology: It was a cross sectional study done on 270 adults , 160 males and 110 females at Ziauddin University Hospital, Clifton, Karachi using CT Para nasal sinuses. The depth of olfactory fossa was evaluated by measuring the height of lateral lamina of cribriform plate. Results: The mean and standard deviation(SD) of right olfactory fossa depth was greater than that of left 6.184±1.8237mm and 5.949 ±1.8003mm (p value 0.006) respectively. Mean ± (SD) for left olfactory fossa depth was greater in females (6.215±1.9271) than in males (5.766±1.6896) (p value 0.043). Keros type II was found to be the most frequent on both right and left sides that is, in 69.26% and 72.96% individuals respectively followed by type III on right side in 18.15% and on left side in 15.19% subjects. Type I was found to be the least frequent in our population with a value of 12.59% on the right side and 11.85% on the left side. Conclusion: Our study shows that most of the population falls in the high risk categories of Keros that is type II and type III thus emphasizing the need of preoperative radiological assessment.